MANIFESTATION OF INSIDIOUS TRAUMA IN KAMILA SHAMSIE’S IN THE CITY BY THE SEA - Yadav, Vinay; Singh, Jitender (International Journal of Research -GRANTHAALAYAH, 2025)
This paper explores the manifestation of insidious trauma in Kamila Shamsie’s debut novel, In the City by the Sea. Unlike overt traumatic experiences, insidious trauma operates subtly through systematic oppression, cultural silencing, and inherited fear. Set against the backdrop of political unrest in Pakistan, the novel traces down the young protagonist Hasan’s psychological journey and the portrayal of his family dynamics to expose how political violence permeates everyday life and affects individual consciousness. By analysing narrative representation, hidden layers, and the intergenerational transmission of anxiety, the paper reveals Shamsie’s crafts as a powerful critique of authoritarianism. This study draws theoretical framework from critics like Maria Root and Laura S Brown’s socio-political and cultural theory to explore the hidden traces of trauma emerging from discrimination and exploitation. Hence, the study positions insidious trauma as a lens to understand the invisible scars that haunt societies long after the events themselves.